PERSEPSI DAN PENGALAMAN GURU DALAM PEMANFAATAN ARTIFICAL INTELEGENCE (AI) UNTUK MEDUKUNG PEMBELAJARAN - Amalia, Ria; Amrullah, Roni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of Artificial Intelligence (AI) has had a significant impact on various aspects of life, including education. The presence of AI provides opportunities for teachers to improve the effectiveness and efficiency of teaching and learning activities. This study aims to describe teachers' perceptions and experiences in utilizing Artificial Intelligence (AI) to support Indonesian language learning in Grade VIII at SMP Negeri 3 Selong. This study employed a qualitative approach with a descriptive research design. The research subject was an eighth-grade Indonesian language teacher who had experience using AI to support teaching and learning activities. Data were collected through observation and documentation and analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which consists of data reduction, data display, and conclusion drawing. The findings revealed that the teacher had a positive perception of the use of AI in learning activities. AI was perceived as a technology that facilitates the preparation of teaching materials, the search for learning resources, the development of instructional media, and the design of assessment instruments. The experience of using AI indicated that this technology could improve work efficiency and support the creation of more varied and engaging learning activities. However, several challenges were identified, including the need to verify AI-generated information, the ability to formulate effective prompts, and concerns regarding students' potential dependence on technology. The findings also showed that AI cannot replace the role of teachers in the educational process but serves as a supporting tool in learning implementation. Therefore, the use of AI should be carried out wisely, critically, and responsibly to maximize its benefits for both teachers and students